Lactobacillus amplifies DHAMaR1 conversion to attenuate intestinal ischemia-reperfusion injury via decreasing pyroptosis - Li, Tong; Cai, Hongxing; Qiu, Chenghao; Zhang, Jianbo; Zhou, Shiji; Zhu, Peng; Xian, Wenjing (Frontiers in Immunology, 2025)
BackgroundMaresin1 (MaR1), a specialized pro-resolving mediator derived from docosahexaenoic acid (DHA), exerts potent anti-inflammatory and cytoprotective actions. Its therapeutic relevance and underlying mechanisms in intestinal ischemia–reperfusion (I/R) injury remain to be fully defined.MethodsA murine I/R model was generated by transient occlusion of the superior mesenteric artery. Retinoic acid receptor-related orphan receptor alpha (RORα) and gasdermin D (GSDMD) knockout mice were used to interrogate signaling pathways. Mice received intraperitoneal MaR1 or dietary supplementation with DHA and/or Lactobacillus (Lact). Intestinal injury, inflammation, and pyroptosis were assessed by histology, biochemical markers, and Western blotting. Integrated 16S rRNA sequencing, transcriptomics, and metabolomics characterized microbiota composition, host transcriptional profiles, and metabolic shifts.ResultsMaR1 significantly limited epithelial injury and inhibited pyroptosis through ligand-dependent activation of RORα, effects abolished in Rorα-/- and Gsdmd-/- mice. DHA supplementation elevated systemic MaR1 levels and reproduced protective effects against I/R damage. Remarkably, combined DHA and Lactobacillus supplementation provided synergistic benefits, as Lactobacillus enhanced DHA-to-MaR1 conversion. Multi-omics analyses confirmed coordinated modulation of inflammatory networks and microbial metabolic activity.ConclusionsMaR1 and its precursor DHA confer robust protection against intestinal I/R injury by suppressing RORα-driven pyroptosis. The probiotic-mediated amplification of MaR1 biosynthesis highlights a novel microbiota–lipid mediator crosstalk with translational potential. These findings support combinatorial interventions leveraging host–microbe interactions as a promising therapeutic avenue for ischemic intestinal injury.